Public art projects in exposed social housing areas in Denmark – dilemmas and potentials. Issue 1 (1st January 2021) - Eriksson, Birgit; Sørensen, Anne Scott
ABSTRACT: Western European cultural policies increasingly target marginalized and socially deprived communities. In Denmark, this happens in the political and discursive context of the so-called "ghetto act" (2018), a set of laws and amendments aimed at radically changing low-income public housing neighbourhoods with a high percentage of "non-Western" residents. Consequential, several Danish public housing neighbourhoods undergo drastic renovation and demolition. Simultaneously, cultural governing bodies and institutions approach the neighbourhoods with a variety of publicly funded projects in arts and culture. These are part of a general strategy to reach new audiences / user groups by supporting art manifestations outside the formal art institutions but also of a more specific betterment agenda based on the assumption that the deprived social housing areas can be "elevated" through art and cultural projects. Based on research in four Danish social housing areas in urban margins, the article introduces the social and cultural policies targeting the areas. We identify a triple exposure to social inequality, stigmatization and intervention, and ask how public art projects in the areas interact with and may resist this exposure. From the perspective of Chantal Mouffe's notions of antagonistic politics and dissensual artistic practices, we explore a range of public art projects in four selected social housing areas, and identify four different types of art projects: 1) permanent physical interventions, 2) temporary (re)makings of the neighbourhood, 3) reinforcement of creative skills and agency, and 4) co-inhabitation. Presenting cases from each of these four types, we outline their challenges and potentials. Finally, we discuss how they fit into and/or negotiate the "betterment" agenda and the seemingly neutral vision of the mixed, balanced, or creative city.